Amelioration of Osteoporosis and Hypovitaminosis D by Sunlight Exposure in Hospitalized Elderly Women With Alzheimer's Disease: A Randomized Controlled Trial. (24th June 2015) - Sato, Yoshihiro; Iwamoto, Jun; Kanoko, Tomohiro; Satoh, Kei
Abstract : The JBMR editors express a note of concern that a substantial amount of the text of Sato et al., Amelioration of Osteoporosis and Hypovitaminosis D by Sunlight Exposure in Hospitalized Elderly Women With Alzheimer's Disease: A Randomized Controlled Trial. J Bone Miner Res. 2005;20(8): 1327–1333 (DOI: 10.1359/JBMR.050402 ) is duplicated in Sato et al., Amelioration of osteoporosis and hypovitaminosis D by sunlight exposure in Parkinson's disease (Parkinsonism Relat Disord. 2011;17(1):22‐26 (DOI:10.1016/j.parkreldis.2010.10.008 ). The JBMR editors are reviewing this matter and will inform readers as soon as the review is completed.